Feasibility of a Responsibility-Based Leadership Training Program for Novice Physical Activity Instructors - Toivonen, Hanna-Mari; Hassandra, Mary; Wright, Paul M.; Hagger, Martin S.; Hankonen, Nelli; Laine, Kaarlo; Lintunen, Taru (Frontiers in Psychology, 2021)
Most coaches and instructors would like to teach more than just sport skills to their athletes and children. However, to promote athletes’ or children’s holistic development and teach them to take responsibility and lead, requires the coaches and instructors to first master the skills themselves. Therefore, feasible, high quality leadership training programs where coaches and physical activity instructors are taught to teach and share leadership are needed. The aim of the current study was to evaluate the feasibility of a leadership training program to optimize it and to determine whether to proceed with its evaluation. In the leadership training program, eight Finnish novice physical activity instructors, aged 18 to 22, were taught to promote positive youth development, personal and social responsibility, and shared leadership in a physical activity context. The participants had minimal to no leadership training or experience. The training program consisted of seven meetings totaling 20 h. Helllison’s teaching personal and social responsibility (TPSR) model was the theoretical and practical framework of the training program. Feasibility of the leadership training program was evaluated across four domains of an evidence-based framework: demand, practicality, acceptability, and implementation fidelity. Data of the current complex intervention were collected with application videos, questionnaires, researcher’s log, lesson plans, video recordings, and a semi-structured focus group interview. The quantitative data were analyzed using descriptive statistics and the qualitative data using deductive and inductive content analysis. There was a demand for the leadership training program. The training program was perceived as practical and highly acceptable by the novice instructors and the trainers, and implemented with fidelity, indicating high overall feasibility. No implementation issues were found. Consequently, the current leadership training program has a high probability of efficacy and can be accepted for further evaluation.